Letter to Jane Tolmach from Willie L. Brown Jr. - Willie L. Brown Jr.:::::: (1976)
In a May 19, 1976 letter, Assemblyman Willie L. Brown Jr. thanked Jane Tolmach for including him among her campaign supporters. Although he noted that he was unable to contribute financially at the time, he offered his assistance during the general election. Brown expressed confidence in her campaign strategy and predicted she would win the primary. He suggested meeting after the June 8 election and wished her good luck.